2019
DOI: 10.1155/2019/7614850
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Predicting Disease-Associated LncRNA-MiRNA Pairs Based on the Higher-Order Orthogonal Iteration

Abstract: A lot of research studies have shown that many complex human diseases are associated not only with microRNAs (miRNAs) but also with long noncoding RNAs (lncRNAs). However, most of the current existing studies focus on the prediction of disease-related miRNAs or lncRNAs, and to our knowledge, until now, there are few literature studies reported to pay attention to the study of impact of miRNA-lncRNA pairs on diseases, although more and more studies have shown that both lncRNAs and miRNAs play important roles in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Long non-coding RNAs (lncRNAs) govern fundamental biochemical and cellular processes. To assess more important functional lncRNAs in non-small cell lung cancers (NSCLC), we examined the lncRNA-disease related database LncRNADisease v2.0 ( http://www.rnanut.net/lncrnadisease/index.php/home/search ), which was integrated comprehensive experimentally support and predicted ncRNA-disease associations curated from manual literatures and other resources [ 13 , 35 , 36 ], finding that a latent functional lncRNA, CBR3-AS1, is highly-expressed in NSCLC. To further validate the obtained results in database, we detected the expression of lncRNA CBR3-AS1 in three subtypes of NSCLC, 60 LAD, 40 LCC and 40 LSCC patient tumor tissues compared with its normal specimens.…”
Section: Resultsmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) govern fundamental biochemical and cellular processes. To assess more important functional lncRNAs in non-small cell lung cancers (NSCLC), we examined the lncRNA-disease related database LncRNADisease v2.0 ( http://www.rnanut.net/lncrnadisease/index.php/home/search ), which was integrated comprehensive experimentally support and predicted ncRNA-disease associations curated from manual literatures and other resources [ 13 , 35 , 36 ], finding that a latent functional lncRNA, CBR3-AS1, is highly-expressed in NSCLC. To further validate the obtained results in database, we detected the expression of lncRNA CBR3-AS1 in three subtypes of NSCLC, 60 LAD, 40 LCC and 40 LSCC patient tumor tissues compared with its normal specimens.…”
Section: Resultsmentioning
confidence: 99%
“…It can degrade mRNA, inhibit translation and protein synthesis, and regulate genes by binding to the 3’-untranslated regions (3’-UTR) of mRNA. 4 , 5 MiRNA has been proved to play an important role in biological growth and development of organisms, metabolism and the occurrence and development of diseases. 6 Studies have shown that miRNA can be released from cells and participate in inflammation and tissue damage.…”
Section: Introductionmentioning
confidence: 99%